Normative Juridical Analysis of Marriage Without a Guardian in the Practice of Unregistered Polygamy Reviewed from Islamic Law and Indonesian Positive Law - Akbar, Alfikrul; Ahsanul Mufid (Cv. Kayaswara, Indonesia, 2025)
This inquiry examines the legal standing of matrimonial unions contracted in the absence of a guardian within the landscape of officially unregistered polygamous arrangements, appraising them through the converging lenses of Islamic jurisprudential tradition and Indonesia's statutory architecture. Deploying a normative juridical methodology enriched by legislative, doctrinal, and case-oriented analytical pathways, the investigation draws upon Quranic scripture, Prophetic narrations, the national marriage statute of 1974, the codified Islamic legal compendium, and pertinent adjudications from religious tribunals accessible via the apex court's digital repository. The analysis substantiates the preponderant scholarly consensus, particularly in the Shafi'i tradition that pervades the Indonesian archipelago, that the guardian is a non-negotiable constituent of marital validity. National legislative provisions mirror this stance, rendering guardianless unions legally deficient. Concurrently, solemnizing a polygamous bond without spousal acquiescence and judicial endorsement contravenes multiple statutory imperatives. The investigation culminates in establishing that the confluence of these twin procedural shortcomings generates compounded juridical vulnerabilities: prospective retroactive nullification, erosion of spousal civil protections, and precarious legal standing for progeny.